2020
DOI: 10.1177/2472555219860779
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive and Selective Immunoassay for the Quantitation of Serum Latent Myostatin after In Vivo Administration of SRK-015, a Selective Inhibitor of Myostatin Activation

Abstract: Myostatin, a member of the transforming growth factor β (TGFβ) superfamily, is a key regulator of skeletal muscle mass and a therapeutic target for muscle wasting diseases. We developed a human monoclonal antibody, SRK-015, that selectively binds to and inhibits proteolytic processing of myostatin precursors, thereby preventing growth factor release from the latent complex. As a consequence of antibody binding, latent myostatin accumulates in the circulation of animals treated with SRK-015 or closely related a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…This relationship suggests that apitegromab doses at above 3 mg/kg allow for full engagement of latent myostatin, and higher doses allow for longer duration of full target engagement. These results are consistent with trends seen in both cynomolgus monkeys treated with apitegromab [25] and in an SMND7 mouse model of SMA after treatment with the parental muSRK-015P molecule [21].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This relationship suggests that apitegromab doses at above 3 mg/kg allow for full engagement of latent myostatin, and higher doses allow for longer duration of full target engagement. These results are consistent with trends seen in both cynomolgus monkeys treated with apitegromab [25] and in an SMND7 mouse model of SMA after treatment with the parental muSRK-015P molecule [21].…”
Section: Discussionsupporting
confidence: 88%
“…The bioanalytical assay used to measure serum latent myostatin implements an acid-dissociation step to dissociate the drug-antigen complex, allowing for the quantitation of total serum latent myostatin [25]. In part A (SAD) of the study, serum latent myostatin levels increased and peaked at about 2000-3000 ng/ mL by days 14-28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results were partially confirmed by the SomaScan aptamer technology measurement of samples from two large cohort studies in which, however, sarcopenia was not assessed [ 110 ]. Further research investigated various, specific myostatin measurement methods, such as immunoassays, immunoradiometric sandwich assay, antibody-free assay and liquid chromatography-tandem mass spectrometry assay combined with immunoprecipitation [ 111 , 112 , 113 , 114 ]. These new, specific assays could be used to clarify discrepancies in earlier results, as well as serve as a validation tool for commercially available methods.…”
Section: Myostatin and Muscle Wastingmentioning
confidence: 99%
“…Target engagement with apitegromab in cynomolgus monkeys and rats. Target engagement with apitegromab has previously been confirmed in pharmacology studies in rodents 11 and cynomolgus monkeys, 24 wherein apitegromab exposure led to increased circulating levels of latent myostatin. In our current studies, we confirmed the target engagement with apitegromab by measuring serum latent myostatin levels across the dosing and recovery phases (Figure 4).…”
Section: Multidose Toxicokinetics Of Apitegromab In Cynomolgus Monkeys and Ratsmentioning
confidence: 83%